The Relationship between Age and Occupation with Hypertension in Sungaibuntu Village in 2023: Hubungan Usia dan Pekerjaan dengan Kejadian Hipertensi di Desa Sungaibuntu Tahun 2023 - Iha Nursolihah; Dian Agnesa Sembiring; Istiana Faizah Aulia; Ikrimah Fitri Ramadhanti; Salwa Adelia Putri; Almira Shidqi Indirajati (JOHAR (Journal of Hospital Administration Research), 2024)
Introduction: The World Health Organization (WHO) states that one in three people is diagnosed with hypertension, and only 36.8% of them are undergoing treatment. In Indonesia, the age group with the highest hypertension is the elderly. Research Objective: To determine the relationship between age and occupation with the incidence of hypertension in Sungaibuntu. Research Method: Quantitative analytical research with a cross sectional research design, using primary data through questionnaires and blood pressure measurements on research respondents, namely residents of Sungaibuntu. Research Results: There is a significant relationship between age and systolic blood pressure (p=0.0001), and there is a significant relationship between age and diastolic blood pressure (p=0.018). Meanwhile, for the work variable, there was no relationship between work and systolic blood pressure (p=0.335), and there was no significant relationship between work and diastolic blood pressure (p=0.223). Conclusion: There is a positive correlation between age and systolic blood pressure and age and diastolic blood pressure, meaning that the higher the age, the higher the incidence of hypertension. Meanwhile, work was not related to the incidence of hypertension in respondents in Sungaibuntu.